REVITALISASI FUNGSI BAHASA DALAM ERA GLOBALISASI: SEBUAH TINJAUAN HAKIKAT BAHASA (Journal Edutama Multidisciplinary Indonesian, 2025)
Language serves as the foundation of human communication and acts as a cultural identity that shapes and distinguishes communities. In the era of globalization, the function of language has undergone significant shifts due to the flow of information, technology, and the dominance of international languages. This paper reviews the nature of language from both functional and philosophical perspectives and offers a revitalization approach to address global challenges. Using a qualitative-descriptive method, this journal highlights the importance of preserving mother tongues, the role of educational institutions, and cultural collaboration as strategic efforts to maintain the function of language amid global modernity